Criminal Policy in Combating Digital Banking Crime: Challenges and Prevention Strategies - Harlina Hamid; Muhammad Fadli Faisal Rasyid (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Digital transformation in the banking sector has introduced numerous conveniences in financial transactions, yet simultaneously opened opportunities for increasingly sophisticated and damaging new forms of crime. This article comprehensively analyzes criminal policy in combating digital banking crime in Indonesia, exploring the legal, technological, and institutional challenges faced, and formulating effective prevention strategies. Through systematic literature review and critical policy analysis, this research demonstrates that digital banking crime in Indonesia has experienced significant increases both in quantity and complexity of modus operandi, encompassing phishing, skimming, hacking, social engineering, banking trojan malware, and various technology-based fraud schemes. Financial losses amount to trillions of rupiah annually, excluding the psychological impact on victims and erosion of public trust in digital banking systems. Research findings identify fundamental challenges in combating digital banking crime, including limitations in legal frameworks that have not fully accommodated technological developments, gaps in law enforcement capacity for cyber investigation, complexity of evidence in digital cases, complicated cross-border jurisdiction, rapid evolution of crime modi outpacing regulatory adaptation, and low digital security literacy among banking service users. Policy analysis shows that penal approaches through criminalization and law enforcement, while important, are insufficient without comprehensive non-penal strategies.